2022
DOI: 10.1371/journal.pone.0266951
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac remodeling in ambitious endurance-trained amateur athletes older than 50 years–an observational study

Abstract: Background Data on cardiac remodeling in veteran athletes are conflicting but of clinical importance. Methods Sixty-nine clinically stable and healthy individuals >50 years were identified (median 55 (IQR 52–64), 26% female). Echocardiographic features were identified in individuals, who have performed endurance sports at 70% of their maximum heart rate for at least 1 hour 3 times/ week over the previous 5 years. Results Median training time in all participants was 6 hours per week. Therefore, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Recently, it has been observed that a troponin exerciseinduced increase above the 99th percentile could be an early marker of mortality and cardiovascular events (27) notably in participants with hypertension (28). Nevertheless, these results remain to be discussed (7,26,29,30). To date, no study has reported a relationship between echocardiographic characteristics and cardiac biomarkers in long distance runners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been observed that a troponin exerciseinduced increase above the 99th percentile could be an early marker of mortality and cardiovascular events (27) notably in participants with hypertension (28). Nevertheless, these results remain to be discussed (7,26,29,30). To date, no study has reported a relationship between echocardiographic characteristics and cardiac biomarkers in long distance runners.…”
Section: Introductionmentioning
confidence: 99%
“…This increase of practice has also been observed among individuals older than 45 years old, currently representing around 50% of the participants in marathons and long-distance running races ( 3 ). Beneficial cardiovascular effects of moderate exercise are recognized ( 4 ), while cardiovascular effects of prolonged and intense exercise remains debated ( 5 7 ). Physical activity such as long-term endurance sport practice induces a cardiac remodeling named “athlete’s heart”( 8 10 ), mainly concerning the left ventricle (LV), but also right ventricle (RV) by inducing right ventricular remodeling ( 11 ), even if clinical significance is unclear ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%